Urgensi Penemuan Hukum dan Penggunaan Yurisprudensi dalam Kewenangan Mahkamah Konstitusi - Imam Sujono (The Constitutional Court of the Republic of Indonesia, 2021)
Indonesia is a democratic state based on law (constitutional democratic state), with understanding that Constitution has a position as the supreme law, because the whole administration of the state should be based on the Constitution. The Constitutional Court was present as the guardian of the constitution to realize realization of ideals of Indonesia as a democratic state based on law. The research entitled Rechtsvinding and Jurisprudence Used by the Constitutional Court examines the importance of rechtsvinding and the attachment of using jurisprudence in deciding cases according to the authority possessed by the Constitutional Court. This research uses the Socio Legal method, which is a research method that examines a problem through normative analysis, then uses a non-legal science approach that develops in society. The results of the research that has been done are; 1) penemuan law by the Constitutional Court interpreted as an effort to how the Constitutional Court interpreting the Constitution (1945), testing the laws against the 1945 Constitution, to decide the other cases the authority granted by the 1945 Constitution, 2) The Constitutional Court there is no obligation to be bound and is not there is a prohibition to use the jurisprudence of the Supreme Court and other courts under its environment as well as the jurisprudence of the Constitutional Court itself.